Predictors of quality of childcare centers in low-income settings: findings from a cross-sectional study in two Nairobi slums - Nampijja, Margaret; Langat, Nelson; Oloo, Linda; Okelo, Kenneth; Muendo, Ruth; Kiyeng, Martin; Amboka, Patrick; Abboah-Offei, Mary; Ray, Anna; Kitsao-Wekulo, Patricia; Kimani-Murage, Elizabeth W.; Elsey, Helen (Frontiers in Public Health, 2023)
Background: Rapid urbanisation and increased women involvement in paid work has contributed to the upsurge of informal childcare centres especially in low-income settings where quality is a major issue. However, there are limited data on the factors associated with quality of childcare centres in informal settlements in Africa.We conducted a quantitative observation and questionnaire survey of 66 childcare centres to identify the factors associated with quality of childcare services in two informal settlements (Korogocho and Viwandani) in Nairobi. The quality of the centres (outcome variable) was assessed using a locallydeveloped tool. Data on centre characteristics including type, size, location, length of operation, charges and number of staff were collected. Centre providers' knowledge, attitude, and practices (KAP) in childcare were assessed through a questionnaire focusing on nurturing care, and business management. Data were described using means and standard deviation or frequencies and percentages. Associations between quality center score (outcome variable) and other variables were examined using multivariable linear regression to identify potential predictors of the quality of the center environment.Findings: A total of 129 childcare centres were identified and categorised as home-based (n=45), centre-based (n=14), school-based (n=61) and church-based (n=9). The number of home-based centres was particularly high in Viwandani (n=40; 52%). Only 9% of home-based centres reported any external support and 20% had any training on early childhood development. Sixty-six centres had complete detailed assessment for predictors of quality reported here. Unadjusted linear regressions revealed associations between quality of childcare center and centre provider education level, type of centre, support received, caregiver-child ratio, number of children in the centre, and centre provider KAP score (p<0.05). However, in the multivariable regression, only higher levels of centre provider KAP (𝛽=0.51; 95% CI: 0.18, 0.84; P=0.003) and centre type (𝛽=8.68; 95% CI: 2.32, 15.04; P=0.008) were significantly associated with centre quality score.Implication: Our results show that centre provider knowledge and practices are a major driver of quality of childcare centres in informal settlements in Nairobi. Interventions for improving the quality of childcare services in such settings should invest in equipping centre providers with the necessary knowledge and skills through training and supportive supervision.